Genealogía de Los mexicanos pintados por sí mismos - Pérez Salas C., María Esther (El Colegio de México, A.C., 1998)
This article deals with the  external process that decisively influenced the publishing of Los mexicanos pintados por sí mismos (Mexicans portrayed by themselves), represented by the European romantic movement. It analyzes particularly the development of the literary style of costumbrismo in its more romantic vein, which generated a series of illustrated works whose central theme were popular groups, and which influenced Mexican literary and graphic production during the first half of the nineteenth century. The article also notes that the model imposed by England, France and Spain, where image and text became an indissoluble binomial in the treatmentt of popular groups, was applied in our country with certain changes, which gave the 1854 Mexican edition a specificity that distinguishes it from its previous homologues.